Does Local Diversity Affect Charitable Giving? - Baris Yörük (Institute of Labor Economics (IZA), 2025)
How does diversity affect charitable giving? On the one hand, diversity can lead to increased charitable giving, as individuals may feel more connected to and invested in their community when they see the diversity of needs and perspectives within it. On the other hand, diversity can also create challenges for charitable giving, as individuals may have different priorities, beliefs, and cultural norms that affect their willingness to give to certain causes and organizations. Using data from 2010-2020 county-level income tax returns linked to the U.S. Census population estimates, I find a negative impact of local ethnic diversity on charitable giving. In particular, I document that a one percentage point increase in the local ethnic fragmentation index is associated with up to a 2.9 percent decrease in the fraction of tax returns with charitable contributions and a 2 percent decrease in charitable contributions as a fraction of adjusted gross income.
Keywords: J10; J18; H30; 330; charitable giving; local ethnic diversity; fundraising